Novel debittering process of green table olives: application of β-glucosidase bound onto superparamagnetic nanoparticles. Issue 1 (1st January 2018) - Savas, Elif; Kaya, Mihrap Yaşar; Karaagac, Oznur; Onat, Serhat; Kockar, Hakan; Yavas, Hakan; Kockar, Feray
ABSTRACT: In this work, the olive β -glucosidase ( β -glu) enzyme was immobilized onto superparamagnetic nanoparticles (SPMNs). Moreover, immobilized enzyme was also used for the debittering process for natural edible olives from Edremit, Turkey. Owing to SPMNs, the system can be easily removed by a simple magnet and reused many times for debittering process. The free olive β -glucosidase (E), β -glucosidase bound SPMNs (IE), free commercial β -glucosidase (CE), and commercial β -glucosidase bound SPMNs (ICE) were comparatively studied for oleuropein removal. In 6 h, the treatment of E, IE, and ICE hydrolyzed the 15.8%, 56.4%, and 80.0% of the oleuropein for 1000 g of olives, respectively, and further treatment showed that the IE and ICE reached the 100% after 22 h treatment. The results revealed that the IE and ICE with biocompatible properties of SPMNs have the economical, fast, and reusable properties for the industrial debittering process in the table olive production.